Analytical and Spectral Studies on Multi-use Hydrocarbanaceous Plant Species of Western Ghats, Tamil Nadu, India - Augustus, G.D.P.S.; Rajarathinam, K.; Kumari, G.D.S.; Kannan, D.; Jayabalan, M. (Asian Journal of Chemistry, 2016)
Large-scale screening of plants growing in the Western Ghats, Tamil Nadu, India was conducted to assess the hydrocarbon production and the type of isoprene compound(s) present. Three species contained more than 3% hydrocarbon. Sarcostemma brevistigma had the highest concentration of hydrocarbon with 3.6%. Seven species contained more than 2% of hydrocarbons amount the plant species screened. The hydrocarbon fraction of Ficus elastica (leaf) had a gross calorific value of 9834 cal/g (41.17 MJ/kg), which is close to the calorific value of fuel oil. Six-hydrocarbon fraction contained gross calorific value of more than 9000 cal/g (37.68 MJ/kg). Of the 13 species hydrocarbon fraction analyzed, seven species contained cis-polyisoprene compounds, while two species contained trans-polyisoprenes. Cis and trans polyisoprenes are potential alternative energy sources for fuel and/or as industrial raw materials.